Implementasi National Single Window (Airportnet) dalam Upaya Mendukung Pelayanan Kargo Udara di Bandar Udara Soekarno Hatta – Cengkareng - Mugihono, Dina Yuliana (Warta Penelitian Perhubungan, 2019)
Implementation of National Single Window (Airportnet) as an Attempt to Support Air Cargo Service in Soekarno Hatta Airport - Cengkareng :The Director General of Air Transportation has handed over the implementation and responsibility of the information service system for the exported and imported goods at the airport (NSW-Airportnet) to the service handling committee of information system on the export and import of goods under Authority Office of Soekarno Hatta Airport. The purpose of the study was to determine the implementation of National Single Window airport (NSW-airportnet) system and the perception of the warehouse in the implementation of an National Single Window (NSW) system of the airport (NSW-airportnet). The sampling collection technique used purposive sampling that met the criteria of expert judgment. Analysis techniques used CSI, Fish Bone Analysis, and USG Method. The results of the study indicate that the National Single Window Airport (NSW-airportnet) at Soekarno Hatta Airport is currently in an inoperative condition. The causes for inoperative condition is the person, system and support; meanwhile, the root problem is data communication and non-synchronous data formats, lack of the support from management cooperation and stakeholders, data integration are unavailable, warehouse has not yet inputted the data, interconnection and equipment are inactive, lack of staff commitment, no SOP of airportnet maintainance system, the maintenance and maintenance budget allocation is still at the head office. The conformity level of NSW Airportnet implementation is 47.5% with the customer satisfaction index (CSI) of 42.78% (less satisfied). Keywords: National Single Window (NSW), airport, warehouse, CSI, fish bone analysis, USG Methods. Direktur Jenderal Perhubungan Udara telah menyerahkan pelaksanaan dan tanggung jawab sistem layanan informasi arus barang ekspor dan impor di bandar udara (NSW-Airportnet) pada komite penanganan kegiatan sistem layanan informasi arus barang ekspor dan impor di bawah Kantor Otoritas Bandar Udara Soekarno Hatta. Tujuan dalam penelitian adalah untuk mengetahui pelaksanaan sistem National Single Window bandar udara (NSW-Airportnet) dan persepsi warehouse dalam pelaksanaan sistem NSW bandar udara (NSW-Airportnet). Teknik pengambilan sampel menggunakan purposive sampling yang memenuhi kriteria expert judgement. Teknik analisis menggunakan indeks kepuasan pelanggan (CSI), Analisis Fish Bone dan metode Urgency, Seriousness, Growth (USG). Hasil penelitian menunjukkan bahwa saat ini NSW Bandar Udara (NSW-Airportnet) di Bandara Soekarno Hatta dalam kondisi tidak beroperasi. Penyebab tidak beroperasinya adalah person, system dan support sedangkan akar masalahnya yaitu tidak sinkronnya komunikasi data dan format data, kurangnya dukungan manajemen kerjasama dan stakeholders, tidak adanya integrasi data, warehouse sudah tidak menginput data, interkoneksi dan peralatan sudah mati, masih kurangnya komitmen petugas, belum adanya SOP pemeliharaan sistem Airportnet, alokasi anggaran pemeliharaan dan perawatan masih berada di kantor pusat. Tingkat kesesuaian implementasi NSW Airportnet sebesar 47,5% dengan CSI sebesar 42,78% (kurang puas).Kata kunci: National Single Window (NSW), Bandar Udara, Warehouse, CSI, Analisis Fish Bone, Metode USG.